Competing Public Values Amidst Fiscal Crisis: The Case of State Takeover System in Michigan. Issue 8 (September 2022) - Jun, Kyu-Nahm; Moldavanova, Alisa
The article analyzes contested reasoning and public values conflict in the state takeover of municipalities via emergency managers (EM) to address fiscal crisis. We investigate the following questions: (1) which public values are associated with the EM intervention strategies?; (2) is there a competition among those values? A content analysis of nearly 500 official documents in four Michigan municipalities reveals that EM interventions reflect a strive for fiscal accountability and legality at the expense of democratic values. This study contributes to the growing body of research on public values, and it advances our understanding of decision-making processes under stress.